The Use of Cohesive Devices in the Narrative Texts of the 11th Graders - Lestari, Nurbaeti; Sutopo, Djoko (English Education Journal, 2020)
Writing is one of the skills learned by 11th graders. It makes the students consider to make their text communicative to the readers. To recognize whether the students can communicate the text or not, one can analyze its cohesive devices. This study aimed to find out the use of cohesive devices in narrative texts written by 11th graders of Pelita Bangsa School. Qualitative method was used in this study. Five texts were chosen by the researcher from 11th graders of Pelita Bangsa School Cirebon. The analysis focused on students’ texts analyzed by the theories of Halliday and Hasan (1976) and Thornbury (2005). The findings showed that reference, conjunction, substitution, ellipsis, and lexical cohesion were used by the students. However, both substitution and ellipsis were infrequently used by the students. Meanwhile, reference and conjunction were frequently used by the students. In addition, the relationship of the devices in achieving text coherence was important. Cohesive devices create a text that makes sense to read. In conclusion, some cohesive devices were familiar to the students, only substitution and ellipsis were rarely used by them. Moreover, the relationship of cohesive devices in achieving text coherence was the direct involvement of all cohesive devices in making text coherence.